Mitochondrial Dynamics: An Emerging Paradigm in Ischemia-Reperfusion Injury - Calo, Lesley; Dong, Yi; Kumar, Rita; Przyklenk, Karin; H. Sanderson, Thomas (Current Pharmaceutical Design, 2013)
Cardiomyocytes and neurons are highly susceptible to ischemia-reperfusion injury; accordingly, considerable effort has been devoted to elucidating the cellular mechanisms responsible for ischemia-reperfusion-induced cell death and developing novel strategies to minimize ischemia-reperfusion injury. Maintenance of mitochondrial integrity is, without question, a critical determinant of cell fate. However, there is emerging evidence of a novel and intriguing extension to this paradigm: mitochondrial dynamics (that is, changes in mitochondrial morphology achieved by fission and fusion) may play an important but as-yet poorly understood role as a determinant of cell viability. Focusing on heart and brain, our aims in this review are to provide a synopsis of the molecular mechanisms of fission and fusion, summarize our current understanding of the complex relationships between mitochondrial dynamics and the pathogenesis of ischemia-reperfusion injury, and speculate on the possibility that targeted manipulation of mitochondrial dynamics may be exploited for the design of novel therapeutic strategies for cardio- and neuroprotection.
Keywords: brain